Personality and vocational interests of creative adolescents from racial and ethnic minorities. Issue 1 (3rd July 2019) - Vuyk, M. Alexandra; Kerr, Barbara A.
ABSTRACT: This study examined personality and vocational interests in creative adolescents from racial and ethnic minority groups in the Midwest, identified with a profiling method developed based oncharacteristics that eminent creative individuals presented inadolescence. Participants included 97 students from different racial and ethnic minority groups, whose personality and vocational interests were described and compared using the Six Factor Personality Questionnaire (SFPQ), and the Vocational Preference Inventory (VPI). Participants from all racial and ethnic groups displayed similar personality traits and vocational interests, consistent with creative adults; scoring highest in Openness to Experience, Extraversion, Artistic and Investigative interests, and scoring lowest in Agreeableness, Conscientiousness, and Conventional interests. No significant multivariate differences emerged between racial and ethnic minority groups. These results point to the existence of a cross-cultural creative personality and vocational interests, likely following the pattern of convergence-divergence in different creativedomains observed in eminent individuals from racial and ethnicminorities.